Real and monetary effects of an exogenous change in interest rates - rejoinder - Thom, DR (Economic & Social Studies, 1974)
Honohan seems to be treating my model as being both analytically and operationally equivalent to the standard Mundell open economy model. This I believe to be a misconception.
Keywords: Interest Rates; Ireland